The untranslated leader of nuclear COX4 gene of Saccharomyces cerevisiae contains an intron. - Schneider, J C (1987)
The nuclear gene for subunit IV of cytochrome oxidase (COX4) in Saccharomyces cerevisiae contains a 342 bp intron which is contained entirely within the 5' leader of the message. Splicing of the intron results in removal of several small open reading frames; subsequently, the COX4 AUG becomes the 5' proximal initiation codon. A strain with an rna2- mutation fails to splice mRNA efficiently at restrictive temperature and was used to map the intron splice junctions by RNase protection. Two major mRNA initiation sites were mapped by primer extension of synthetic oligodeoxynucleotides. The splice junctions and internal TACTAAC box conform to consensus sequences previously determined from other yeast introns. One gene for subunit V of cytochrome oxidase (COX5b) has also been shown to contain an intron. The significance of introns in two nuclear genes encoding subunits of cytochrome oxidase is discussed.